High Efficiency Single Phase Photovoltaic Based Pulse Width Modulated Transformerless Inverter Tied to Grid (International Journal of Scientific Research in Science and Technology, 2024)
Nowadays the emergence of renewable energy sources is an outcome of the rapid rise in power consumption. PV power generating systems are more effective and superior to other renewable sources for energy as compared to other sources. Numerous studies are expected to contribute to the widespread implementation of PV in power systems. Modern transformer-less inverter technologies are proving to be more dependable and efficient than traditional ones because of their incredibly appealing cheap cost, reduced weight, and smaller size, that all contribute to enhanced efficiency. This research proposes a new type of transformer less inverter that is inexpensive and more effective than traditional transformer-based inverters. In this paper the transformer less inverter for photovoltaic systems linked to the grid has ability to lower the leakage currents. The detailed analysis of proposed topology and obtained results are analyzed in MATLAB simulation.